Pertumbuhan dan Potensi Produksi Beberapa Genotipe Jarak Pagar (Jatropha curcasL.) di Tanah Masam - Indah Retnowati; Memen Surahman (Departemen Agronomi dan Hortikultura, 2013)
Indonesia has extensive acid soil but its utility is still limited because of its low nutrient content. Jatropha is a plant which can grow on various soil types, includes on marginal one, and has used as raw material for biodiesel. Therefore, the growth of jatropha on acid soil need to be studied as an effort for developing jatropha and utility of acid soil in Indonesia. To initiate the effort, research to grow various jatropha genotypes on acid soil was done. The objectives of this research was to obtain a potential tolerant jatropha genotype for acid soil. The research was conducted at UPTD Development of Dryland Technology at Singabraja Village, Tenjo Subdistrict, Bogor, West Java, from November 2010 – August 2011. This research using Randomized Complete Block Design (RCBD) with jatropha genotype as factor. The result showed that there were differences in growth among the jatropha genotypes. There are five jatropha genotypes with better growth in acid soil (pH 5.0) compare to others, i.e. Medan I-5-1, Dompu, IP-2P-3-4-1, Sulawesi, and Bima M.Keywords: physic nut, genotypes, Jatropha curcas, acid soil